Proposed Business Strategy to Increase Asset Under Management (AUM) Growth: Case of ZYZM CORP - Oki Fimansyah Wiyatno; Anh-Dung (Andy) Do (AIBPM Publisher, 2021)
In the second quarter of 2020, Indonesia's economy has worsened to the point where it is on the edge of recession due to Covid 19. The contracted Indonesian economy, rising competition, fraud cases, and shifting investor generations certainly caused turmoil in the capital market, especially the mutual fund industry. These conditions are also felt by ZYZM CORP as an investment management company as their Asset Under Management (AUM) decreased by 12% in 2020. Therefore, this paper aims to formulate a new business strategy for ZYZM CORP to overcome various challenges to successfully increase AUM. Strategy formulation is carried out using a combination of general reviews such as environmental analysis, internal analysis using the VRIO framework, interviews with the company’s relevant stakeholders, and questionnaires to the capital market investors. The results show that ZYZM CORP must overhaul its business strategy by making improvements to its internal resources, maintaining the relationship, and continuing to broaden cooperation with the various mutual fund selling agent (APERDs), improving customer service, retargeting the customer segment to millennial retail investors, and continuing to maintain and actively communicate ZYZM CORP's Good Corporate Governance (GCG) to increase investor confidence to invest in ZYZM CORP products.